Território e políticas de sustentabilidade no Complexo Energético Amador Aguiar Rio Araguari/MG - Lima, Hudson Rodrigues (2013)
This qualitative research focused attention on the surroundings of the two reservoirs of Energetic Complex Amador Aguiar I and II, in the municipalities of Uberlândia, Araguari and Indianópolis in the State of Minas Gerais, Brazil. Sought in the bibliographic data surveys, documentary and narratives of people, highlighting the business sustainability discourse of Capim Branco Energy Consortium (CCBE) and in the laws of municipal administrations and your territorialisation in the area surrounding the Energy Complex Amador Aguiar. Sought to relate precious concepts to Geography, such as space and territory, with the concept of Economic Institutionalism, particularly discussions pertaining to New Economic Sociology, looking for evidence of governances strategies of space-territory of people affected by dams. Added to this search for understanding of the operation of a Large Hydropower Investment Project in the light of a critical discourse conception of sustainable development and sustainability, taking into account the principles of deep ecology and scholars of Ecomarxism. At the intersection of speeches and corporate practices, municipal and communities affected, explained the emptying of meaning of an idea such as sustainable development, pointing to the need of public authorities and Private initiative established democratic and participatory power relations in the definitions and implementations of programs, projects, plans and actions that effectively build a healthy territorial development respecting human life, the life of animals and plants.